Quality Of Financial Statements Affected By Influence Of Leadership And Application Of Accounting Information Systems (Surveys In The Data Processing Center And Tax Revenue Center Of The Directorate General Of Taxation Of The Ministry Of Finance Of The Republic Of Indonesia) - Endraria, Endraria; Kusuma Prayoga, Lutfi (Opción, 2019)
This study aims to determine the effect of leadership and application of ac- counting information systems on the quality of financial statements (surveys in the data processing center and tax revenue center of the Directorate Gener- al of Taxation of the Ministry of Finance of the Republic of Indonesia) where this type of research is quantitative research in the form of explanatory, quan- titative research is a form of explanatory or problem solving model and analy- sis conducted using statistical analysis empirically to examine the relationship between research variables with the population in this study are employees in the data processing center and income center taxation directorate general taxation ministry of finance of the Republic of Indonesia) 80 people and with a sample that used in this study were 67 respondents. Based on the results of the study it can be concluded that there is an influence of leadership and applica- tion of accounting information systems on the quality of financial statements (survey at the data processing and taxation center of the Ministry of Finance of the Directorate General of Finance of the Republic of Indonesia)